Allergic seasonal blepharoconjunctivitis therapy optimization in conditions of dry eye and meibomian glands dysfunctions - S. V. Yanchenko; A. V. Malyshev; Sh. J. Teshaev; S. S. Davlatov; M. Yu. Odilov; E. A. Haribova; L. M. Petrosyan; R. R. Boboeva (Российский офтальмологический журнал)
Purpose: to evaluate the effectiveness of various therapeutic approaches to the treatment of seasonal allergic blepharoconjunctivitis (SABC) in patients with dry eye syndrome (DES) and meibomian gland dysfunction (MGD). Material and methods. 80 patients with SABC, DES and MGD were examined; 1st-group patients (40 people) received 0.1% olopatodine hydrochloride (2 times a day, 5 weeks), 0.18% sodium hyaluronate (3 times a day, from the 8th day of therapy, 4 weeks) instillations and eyelid hygiene (EH, 2 times a day) — Blefarogel cleansing (5 weeks), Blefarogel-1 (from the 8th day of treatment); 2nd group patients only antiallergic and tear replacement therapy were prescribed. The integral indicators of the conjunctiva and eyelids objective state (C-OS; E-OS), the proportion of MGD and patients with lipid deficiency (LD), OSDI, tear film breakup time (TBUT), the lower tear meniscus heigh (LTMH) and Bijsterveld’s xerosis index (XI) were evaluated before and after therapy. Results. Patients in both groups showed C-OS, E-OS, OSDI, TBUT and XI significant positive changes as a result of therapy. In 1st group patients E-OS, OSDI, TBUT and XI dynamics were significantly more pronounced. Conclusion. In SABC patients in DE and MGD conditions, the approach that included EH in addition to antiallergic and tear replacement therapy turned out to be more effective in influencing the condition of the ocular surface (EOS, OSDI, TBUT, XI), in comparison with the approach based on antiallergic treatment and tear replacement only, which was, probably, associated with a significant decrease in the proportion of MGD and LD as the EH result.